SHAPING THE ACTUAL TEACHER'S PROFILE: HOW ICT CAN INFLUENCE IT? - GABRIEL GORGHIU; LAURA MONICA GORGHIU; ROXANA CONSTANȚA ENACHE; ANA MARIA AURELIA PETRESCU (Studia Universitatis Babes-Bolyai, 2019)
ABSTRACT. In the actual context of massive technological development, the teacher training process ‐ or even, the teacher self‐training one ‐ should be actually based on the acquisition of technical skills, mainly related to the use of Internet and multimedia resources, but also on the didactic skills focused on how to use those resources in order to make the teaching demarche more effective. Generally, in order to introduce ICT in the teaching process, the educators have to go through three distinguish stages of professional development: (a) acquiring the necessary technical skills and introducing ICT for projecting and operationalizing the lessons ‐ even there is an amount of mistrust and fear concerning possible technical and pedagogical problems that may occur; (b) experiencing the ICT implementation in the projected lessons ‐ where the teacher uses the technology to conduct the lessons and improves the teaching process; (c) assessing the ICT resources involved in the lessons or in the possible new ones ‐ ready to be implemented ‐, and drawing related conclusions. ICT can contribute to shape the nowadays teacher's profile, bringing crucial added‐values to the sets of following competencies: (a) communication; (b) information; (c) pedagogical design; (d) production. By introducing ICT in education, it will be clearly reduced the time consumption and repeatability of tasks, offering to teachers the possibility to spend more time on designing lessons in a new and competitive format, performing and evaluating the training process.